Treatment of Parkinson’s disease with biologics that penetrate the blood–brain barrier via receptor-mediated transport - Pardridge, William M. (Frontiers in Aging Neuroscience, 2023)
Parkinson's disease (PD) is characterized by neurodegeneration of nigral-striatal neurons in parallel with the formation of intra-neuronal -synuclein aggregates, and these processes are exacerbated by neuro-inflammation. All 3 components of PD pathology are potentially treatable with biologics. Neurotrophins, such as glial derived neurotrophic factor or erythropoietin, can promote neural repair. Therapeutic antibodies can lead to disaggregation of -synuclein neuronal inclusions. Decoy receptors can block the activity of pro-inflammatory cytokines in brain. However, these biologic drugs do not cross the blood-brain barrier (BBB). Biologics can be made transportable through the BBB following the re-engineering of the biologic as an IgG fusion protein, where the IgG domain targets an endogenous receptor-mediated transcytosis (RMT) system within the BBB, such as the insulin receptor or transferrin receptor. The receptor-specific antibody domain of the fusion protein acts as a molecular Trojan horse to ferry the biologic into brain via the BBB RMT pathway. This review describes the re-engineering of all 3 classes of biologics (neurotrophins, decoy receptor, therapeutic antibodies) for BBB delivery and treatment of PD. Targeting the RMT pathway at the BBB also enables non-viral gene therapy of PD using lipid nanoparticles (LNP) encapsulated with plasmid DNA encoding therapeutic genes. The surface of the lipid nanoparticle is conjugated with a receptor-specific IgG that triggers RMT of the LNP across the BBB in vivo.